UPAYA MENINGKATKAN KESADARAN MASYARAKAT DALAM MENCEGAH PENYAKIT DIABETES MELITUS DI DESA SUMBERSEKAR - Yandriyani, Devilke (Jurnal Bakti untuk Negeri, 2025)
The prevalence of diabetes mellitus both in the world and in Indonesia continues to increase every year. Increasing public knowledge is considered to have an influence on efforts to prevent diabetes mellitus. Extension activities in Sumbersekar village, Malang Regency were carried out by presenting material to the community, specifically Women for Family Empowerment and Welfare (PKK). Increasing public understanding can be seen from active two-way discussions between presenters and participants. These results show that the people of Sumbersekar Village have an interest in understanding and preventing diabetes and the dangers of repeated use of cooking oil. It can be concluded that the aim of this community service, namely to increase public knowledge about preventing diabetes mellitus, has been achieved.